Social engineering warfare as a tactic of information warfare - Groš, Stjepan (European Integration Studies, 2024)
Information warfare encompasses a set of tactics and techniques used to spread disinformation. Adversaries use these strategies to run information operations to manipulate individuals, groups, and society. Owing to the current widespread information warfare, studying the phenomenon to identify effective and efficient means of combating information operations is very important. One prerequisite for the efficient and effective suppression of information operations is an awareness of the tactics and techniques of information warfare. Identifying these tactics and techniques will take some time because of the large number of options at the disposal of those who spread disinformation. This study contributes to this endeavour by analysing social engineering as a technique of information operations. Treating social engineering as a technique of information warfare is a novel approach because social engineering is usually associated with cyber security and is rarely discussed in conjunction with information warfare. We show that social engineering can be used in information operations without requiring significant adaptations. We also argue that social engineering should be treated as a distinct domain and activity, separate from both cyber security and information warfare. While both cyber security and information warfare can use social engineering in their operations, they remain distinct activities that require unique knowledge and skillsets.